An appraisal of primary first-cycle English textbooks - Biniam, Dereje Negede (Ethiopian Journal of Language, Culture and Communication, 2024)
This study aims to examine whether or to what extent the English textbooks in-use in primary first-cycle schools in Ethiopia meet the criteria of good EFL textbook to the age group. The contents of grades 1-4 English textbooks are reviewed qualitatively through adapting criteria developed by Balbi (1997, 2008) and the relevant literature. The research design is descriptive-evaluative. The procedure of analyzing the data starts by reviewing the contents of grades 1-4 English textbooks based on EFL evaluation criteria; it is subsequently followed by finding out how much each item of the checklist meets the criteria of good EFL textbook and concluding the result of the analysis in the form of explaining the reasons why each criterion considered meets the criteria. The result shows that the language contents encompassed in the textbooks are adequate and appropriate to promote students mastery of the English language.